Prevalence and degree of dental fluorosis in schoolchildren aged 8 to 10 years Ferreñafe, Lambayeque - Peru - Mori-Yampufe, Janet Luz (2024)
Objective: The present study was to determine the prevalence and degree of fluorosis in schoolchildren aged 8 to 10years in an educational institution Methodology: It was a quantitative, descriptive, cross-sectional and prospectiveresearch, with a sample of 160 students from 8 to 10 years of age from the Ferreñafe Educational Institution, the data werecollected through clinical evaluation and analysis, with a record sheet based on Dean's Criteria for dental fluorosis. Results:85% of the observed participants had fluorosis, in addition, 56.3% of the children had mild fluorosis, 25% moderate grade,and 13.8% severe fluorosis. Mild fluorosis predominated in both sexes with 58.2% in females and 56.3% in males, and in58.7%, 55.7% and 50% in children aged 8 years, 9 years and 10 years, respectively. Conclusions: The prevalence offluorosis was high, the female sex had a higher prevalence of severe fluorosis and in the male sex the degree of moderatefluorosis, in addition the prevalence of fluorosis decreased with age, which is why the need to evaluate fluoride levels in thecommunity stands out, considering comprehensive approaches in oral health and strategies adapted to each environment.